Transformations of the cyclo-P4 ligand in [Cp′′′Co(η4-P4)]. Issue 26 (2nd June 2020) - Piesch, Martin; Seidl, Michael; Scheer, Manfred
Abstract : The reactivity of the cyclo -P4 ligand complex [Cp′′′Co(η 4 -P4 )] (1 ) (Cp′′′ = 1, 2, 4-tri- tert -butyl-cyclopentadienyl) towards reduction and main group nucleophiles was investigated. Abstract : The reactivity of the cyclo -P4 ligand complex [Cp′′′Co(η 4 -P4 )] (1 ) (Cp′′′ = 1, 2, 4-tri- tert -butyl-cyclopentadienyl) towards reduction and main group nucleophiles was investigated. By using K[CpFe(CO)2 ], a selective reduction to the dianionic complex [(Cp′′′Co)2 (μ, η 3 :η 3 -P8 )] 2− (2 ) was achieved. The reaction of 1 with t BuLi and LiCH2 SiMe3 as carbon-based nucleophiles yielded [Cp′′′Co(η 3 -P4 R)] − (R = t Bu (4 ), CH2 SiMe3 (7 )), which, depending on the reaction conditions, undergo subsequent reactions with another equivalent of 1 to form [(Cp′′′Co)2 (μ, η 3 :η 3 -P8 R)] − (R = t Bu (5 ), CH2 SiMe3 (8 )). In the case of 4, a different pathway was observed, namely a dimerisation followed by a fragmentation into [Cp′′′Co(η 3 -P5 t Bu2 )] − (6 ) and [Cp′′′Co(η 3 -P3 )] − (3 ). With OH − as an oxygen-based nucleophile, the synthesis of [Cp′′′Co(η 3 -P4 (O)H)] − (9 ) was achieved. All compounds were characterized by X-ray crystal structure analysis, NMR spectroscopy and mass spectrometry. Their electronic structures and reaction behavior were elucidated by DFT calculations.